Perancangan Photobook New Normal (Pendekatan Photo Story Deskriptif) - Tanto Trisno Mulyono; Juyo Kemsen Modok (Jurnal Media Komunika, 2021)
For more than a year, Indonesia has been in uncertainty by Coronavirus Disease 2019 (COVID-19). Around March 2020, President Jokowi announced the first case of an Indonesian citizen infected with COVID-19. After the first case was found, this virus spread rapidly throughout Indonesia. To date, more than two million cases have been recorded with more than fifty thousand deaths1. One of the factors for the rapid spread of COVID-19 is the lack of public compliance in implementing a new life (New Normal). After data collection and analysis through library study methods, observations, etc., the authors can find out that a persuasive approach is needed through a media with the delivery of messages that can provide inspiration to further increase public awareness in order to reduce the spread of COVID-19. The result of the collection and analysis is the design of the New Normal Photobook.